(3GdCSGdjH GdcejI aj GdEOGQI (B/s - (3GdaVd, eDjOs ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3eaGgje fXQjI aj GdCSGdjH GdcejI hGJNGP GdbQGQGJ aj efXeGJ GdCYeGd(B- (3GJNGP GdbQGQGJ aj MGdGJ GdHjFjI GdeNJdaI(B- (3GSJNOGe fXQjGJ hCSGdjH eNJdaI aj GJNGP GdbQGQGJ(B- (3GdfeGPL GdQjGVjI aj GdGSGdjH GdcejI(B- (3GdHQeLI GdNWjI(B- (3feGPL eNJdaI ddHQeLI GdNWjI aj GJNGP GdbQGQGJ GdEOGQjI(B- (3CSGdjH GdHQeLjI GddGNWjI aj GJNGP GdbQGQGJ GdEOGQjI(B- (3feGPL Gdfbd GdeaJhM heJYOO GdeQGMd(B- (3GdMGdGJ GdNGUI Hj feGPL Gdfbd(B.s
Keywords: (3GdEMUGAs; (3GdEOGQIs; (3GdCSGdjH GdcejIs